Morphological and Metabolic Parameters of Red Blood Cells after Their Treatment with Ozone - Anna V. Deryugina; Gennady A. Boyarinov; Ionas S. Simutis; Larisa V. Boyarinova; Nikolaii A. Azov (Общая реаниматология, 2018)
The purpose of the study was to assess the morphology of red blood cells (RBC) and the association of morphological parameters with lipid peroxidation processes and the content of organic phosphates in RBC when treating packed red blood cells with the ozonized saline solution (with an ozone concentration of 2 mg/l) after different storage periods.Materials and methods. The morphology of human RBC, the concentration of malonic dialdehyde (MDA) in RBC, the catalase activity, the concentration of ATP and 2,3-diphosphoglycerate (2,3-DPG) were studied before and after treatment of RBC with the ozonized saline (with the ozone concentration of 2 mg/l) after 7, 14, 21 and 30 days of storage.Results. The effect of ozone (2 ng/l) in vitro on the packed red blood cells after 7–21 days of storage contributed to the recovery of RBC shape, increased the concentration of ATP and 2,3-DPG, and optimized the lipid peroxidation. Ozone did not demonstrate a pronounced positive effect on these parameters when the packed RBCs were stored for 30 days.Conclusion. The treatment of the packed RBCs with the ozonized saline solution (with the ozone concentration of 2 mg/l) contributed to the recovery of the discocyte count due to optimization of lipid peroxidation processes in cell membranes and enhanced the synthesis of organic phosphates in cells due to the activation of glycolysis and the pentose phosphate pathway. This can be used to improve the morphological and metabolic status of the packed RBCs before their transfusion.